Can Inflammation-Resolution Provide Clues to Treat Patients According to Their Plaque Phenotype? - Fredman, Gabrielle (Frontiers in Pharmacology, 2019)
Inflammation-resolution is an active process that is governed in part by specialized pro-resolving mediators (SPMs) such as lipoxins, resolvins, protectins and maresins. SPMs, which are endogenously biosynthesized, quell inflammation and repair tissue damage in a manner that does not compromise host defense. Importantly, failed inflammation-resolution is an important driving force in the progression of several prevalent diseases including atherosclerosis. Atherosclerosis is a leading cause of death worldwide and uncovering mechanisms that underpin defective inflammation-resolution and whether SPMs themselves can revert the progression of the disease are of utmost clinical interest. Because atherosclerosis is a disease in which low-grade persistent inflammation results in tissue injury, SPMs have garnered immense interest as a potential treatment strategy. This mini review will highlight recent work that describes mechanisms associated with defective inflammation-resolution in atherosclerosis, as well as the protective actions of SPMs and their potential use as a therapeutic.